B cell-derived nociceptin/orphanin FQ contributes to impaired glucose tolerance and insulin resistance in obesity - Stephanie C. Puente-Ruiz; Leona Ide; Julia Schuller; Adel Ben-Kraiem; Anne Hoffmann; Adhideb Ghosh; Falko Noé; Christian Wolfrum; Kerstin Krause; Martin Gericke; Nora Klöting; Jens C. Brüning; et al. (iScience)
Summary: Immune-derived opioid peptides have been implicated in immune regulation and inflammatory processes. Here, we investigate the effects of nociceptin/orphanin FQ (N/OFQ) on metabolic function and inflammation in obesity. Selectively targeting N/OFQ, encoded by the Pnoc gene, in B cells mitigates the adverse metabolic effects of diet-induced obesity and enhances insulin sensitivity and glucose tolerance. Notably, B cell-specific Pnoc knockout mice display a marked reduction in markers of immune cell migration and diminished macrophage recruitment in adipose tissue and liver. Mechanistically, we identify that N/OFQ promotes macrophage recruitment and metabolic inflammation, exacerbating glucose intolerance and insulin resistance during obesity. Overall, the immunomodulatory properties exhibited by the N/OFQ-NOP system render it a promising therapeutic target for mitigating metabolic inflammation.